Smart Innovations in Communication and Computational Sciences Proceedings of ICSICCS-2018 - Tiwari, Shailesh; Trivedi, Munesh C.; Mishra, Krishn K.; Misra, A. K.; Kumar, Khedo Kavi (Advances in Intelligent Systems and Computing, 2019)
The book presents the latest advances and research findings in the fields of computational science and communication. The areas covered include smart innovation; systems and technologies; embedded knowledge and intelligence; innovation and sustainability; advanced computing; and networking and informatics. It also focuses on the knowledge-transfer methodologies and the innovation strategies employed to make these effective. This fascinating compilation appeals to researchers, academics and engineers around the globe.